Culture and CEO Compensation - Tosi, Henry L.; Greckhamer, Thomas (Organization Science, 2004)
The theory and research on chief executive officer (CEO) compensation tends to be dominated by assumptions and values reflective of those dominant in the national culture of the United States, where most of this work is done. This suggests that an underlying theme focuses on how CEO compensation is related to instrumental choices made in a competitive, capitalist culture. This study seeks to expand the understanding of CEO compensation by examining it in the context of other cultures, based on the premise that national culture plays a significant part in the nature of compensation strategies. We relate cultural dimensions (uncertainty avoidance, power distance, individualism, and masculinity-femininity) developed by Hofstede (Hofstede 1980a, 2001) to several dimensions of CEO compensation. These dimensions are total CEO pay, the proportion of variable pay to total compensation, and the ratio of CEO pay to the lowest level employees. The main findings of our paper are (1) all of the different dimensions of CEO pay were related to power distance, leading us to infer that CEO pay in a culture is most reflective of the strength of the power structure in a society, and (2) total compensation and the ratio of variable pay to total pay are related to individualism. We conclude that cultural dimensions can contribute to understanding cross-national CEO compensation. The implication of this conclusion is that there are different ways that CEO compensation fits into the cognitive schema of various cultures and, furthermore, that these cognitive schema vary across societies that affect the nature of the “cultural matrix into which [money] is incorporated” (Bloch and Parry 1989, p. 1). Moreover, our results imply that particular forms of CEO compensation do not mean the same thing in different cultures, but rather carry different symbolic connotations depending on the values dominant in a society. Thus, not only does the compensation structure of a firm within a culture have a symbolic meaning within organizations (e.g., Trice and Beyer 1993), but it can also be seen as an expression of deeper social values (Hofstede et al. 1990) that may differ across countries.